2021
DOI: 10.1017/s0047404521000130
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two cities: The discursive construction of ‘place’ in gentrifying East London

Abstract: In recent years, the East End of London has been dramatically transformed from a poor, working-class area, to one of the most fashionable neighbourhoods in the world. Adding to a growing body of research which examines the sociolinguistic dynamics of gentrifying neighbourhoods, this article draws on data from two ethnographic projects to examine how young people from the gentrified (i.e. working-class) and gentrifier (i.e. middle-class) communities index place attachment in East London. I demonstrate that for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Sociolinguistics has arguably seen a "place turn" in recent years (Montgomery & Moore, 2017;Cornips & de Rooij, 2018), driven initially by Barbara Johnstone's work on Pittsburghese (e.g., Johnstone, 2004;Johnstone, Andrus & Danielson, 2006), which has captured the ways that class-based linguistic variables in the city of Pittsburgh have come to index place identity over time. Though much sociolinguistic research on place is discursive in nature (e.g., Modan, 2007;Ilbury, 2021), there is evidence that variationist research can benefit from further theorization about place as well. For example, in Becker's (2009) study of the Lower East Side, she found increased rates of nonrhoticity-an iconic New York City feature-when participants discussed neighborhoodspecific topics.…”
Section: Place and Sociolinguistic Variationmentioning
confidence: 99%
“…Sociolinguistics has arguably seen a "place turn" in recent years (Montgomery & Moore, 2017;Cornips & de Rooij, 2018), driven initially by Barbara Johnstone's work on Pittsburghese (e.g., Johnstone, 2004;Johnstone, Andrus & Danielson, 2006), which has captured the ways that class-based linguistic variables in the city of Pittsburgh have come to index place identity over time. Though much sociolinguistic research on place is discursive in nature (e.g., Modan, 2007;Ilbury, 2021), there is evidence that variationist research can benefit from further theorization about place as well. For example, in Becker's (2009) study of the Lower East Side, she found increased rates of nonrhoticity-an iconic New York City feature-when participants discussed neighborhoodspecific topics.…”
Section: Place and Sociolinguistic Variationmentioning
confidence: 99%
“…Gentrifying neighborhoods are frequently accompanied by disagreements over which residents have a legitimate claim to a place, and linguistic practices can play a key role in these disagreements, as can be seen in the increasing attention sociolinguists are giving to gentrification. Most of this work, however, focuses on the speaker's place-making practices in gentrifying contexts, attending to either discourses (Grieser, 2022;Ilbury, 2022;Modan, 2007;Trimaille & Gasquet-Cyrus, 2017), the changing semiotic landscape (Gonçalves, 2019;Leeman & Modan, 2010;Trinch & Snajdr, 2017;Vandenbroucke, 2018), or the shifting indexicalities that emerge as newcomers take up local forms of speech (Johnstone, 2021). While some of these studies do consider uptake, they are primarily concerned with the variation of evaluations and indexicalities of different kinds of speech, while the social and linguistic categories themselves remain constant.…”
Section: Variationist Approaches To Sameness and Differencementioning
confidence: 99%
“…The youth group is based in an East London neighbourhood in Hackney, an inner-city borough (see figure 1) that has historically been associated with high levels of crime and deprivation. Although much of the borough has undergone extensive regeneration (Lees, Slater & Wyly 2008), the estate where Lakeside is based – and where most of the young attendees lived – continues to see higher levels of deprivation than elsewhere (Ilbury 2021).
Figure 1.The Inner East London borough of Hackney (shaded) within the wider conurbation of Greater London (GLA 2020, contains Ordnance Survey data © Crown copyright and database rights)
…”
Section: Research Contextmentioning
confidence: 99%